Attenuated Negative Feedback in Monocyte-Derived Macrophages From Persons Living With HIV: A Role for IKAROS - Faia, Celeste; Plaisance-Bonstaff, Karlie; Vittori, Cecilia; Wyczechowska, Dorota; Lassak, Adam; Meyaski-Schluter, Mary; Reiss, Krzysztof; Peruzzi, Francesca (Frontiers in Immunology, 2021)
Persons living with HIV (PLWH) are at higher risk of developing secondary illnesses than their uninfected counterparts, suggestive of a dysfunctional immune system in these individuals. Upon exposure to pathogens, monocytes undergo epigenetic remodeling that results in either a trained or a tolerant phenotype, characterized by hyper-responsiveness or hypo-responsiveness to secondary stimuli, respectively. We utilized CD14+ monocytes from virally suppressed PLWH and healthy controls for in vitro analysis following polarization of these cells toward a pro-inflammatory monocyte-derived macrophage (MDM) phenotype. We found that in PLWH-derived MDMs, pro-inflammatory signals (TNFA, IL6, IL1B, miR-155-5p, and IDO1) dominate over negative feedback signals (NCOR2, GSN, MSC, BIN1, and miR-146a-5p), favoring an abnormally trained phenotype. The mechanism of this reduction in negative feedback involves the attenuated expression of IKZF1, a transcription factor required for de novo synthesis of RELA during LPS-induced inflammatory responses. Furthermore, restoring IKZF1 expression in PLWH-MDMs partially reinstated expression of negative regulators of inflammation and lowered the expression of pro-inflammatory cytokines. Overall, this mechanism may provide a link between dysfunctional immune responses and susceptibility to co-morbidities in PLWH with low or undetectable viral load.